The Role of Leadership and Employee Empowerment in Improving the Quality of Islamic Higher Education - Hanan, Abdul; Sibaweh, Imam (UIN Sunan Gunung Djati Bandung, 2024)
Higher education in the Cirebon region faces significant challenges in quality, with higher education institutions such as the Institute Pesantren Babakan and Cirebon facing competition. Factors such as infrastructure, curriculum, teaching methods, and human resources contribute to this gap. This study aims to examine leadership mentoring strategies in empowering lecturers and administrative staff at the Institute Pesantren Babakan, Cirebon, in an effort to improve the quality of higher education. A qualitative-participatory approach was used through Participatory Action Research (PTP) at the Institute Pesantren Babakan, Cirebon. The stages included the process of inculturation, problem formulation, strategic planning, program implementation, monitoring, and reflection. Data collection techniques included participatory action, observation, interviews, and documentation. Data were analyzed using a participation-based qualitative analysis method. The findings show a positive relationship between leadership, empowerment, and improving the quality of education. Effective leadership mentoring strategies include leadership training, managerial development workshops, mentoring sessions, and coaching. A holistic approach to empowering lecturers and staff contributes to increased professionalism, motivation, and quality of education. The evaluation showed a positive impact of leadership mentoring on the empowerment of lecturers and administrative staff in IPEBA. The results showed a positive relationship between leadership practices, empowerment of lecturers and administrative staff, and improved educational quality at IPEBA, recommending the adoption of similar approaches in other institutions to achieve similar improvements in educational quality